Functionalization of CVD Grown Graphene with Downstream Oxygen Plasma Treatment for Glucose Sensors. Issue 7 (1st January 2017) - Hadish, Filimon; Jou, Shyankay; Huang, Bohr-Ran; Kuo, Hsiu-An; Tu, Chao-Wei
Abstract : The development of graphene-based devices requires control over the functionalization and modification of the graphene surface. We studied the modification of the monolayer graphene surface with downstream oxygen plasma treatment to form graphene oxide (GO) for use in glucose biosensors. Amperometric and voltammetric methods were applied to GO for glucose oxidase (GOx) immobilization with a simultaneous reduction of GO to reduce graphene oxide. The fabricated glucose sensor shows a sensitivity of 0.118 μA mM −1 cm −2 and a detection limit of 0.0526 mM of glucose. This method provides fast and simultaneous immobilization of GOx and reduction of GO, and can be used in the fabrication of other electrochemical biosensors.